Low-grade polymorphic adenocarcinoma: Atypical case report in the lower retromolar region of the young patient (Research, Society and Development, 2021)
Low-grade polymorph adenocarcinoma (APBG) is a rare malignant neoplasm in the minor salivary gland. It is prevalent in females between the sixth and seventh decade of life. It usually starts asymptomatically, with slow growth and low aggressiveness, and the palate is the most frequent site. Cystic adenoid carcinoma and pleomorphic adenoma are the most frequent lesions that make a differential diagnosis with this neoplasm. Initial therapy should consist of complete surgical excision, with the possibility of association with radiotherapy treatment, with a favorable prognosis depending on the time of diagnosis. This paper aims to report a clinical case of low-grade polymorph adenocarcinoma in a 34-year-old female patient in the lower left alveolar ridge region. Reports of APBG in the posterior inferior alveolar ridge and in patients in the 3rd decade of life are extremely scarce in the specialized literature. It is extremely important for the dentist to know about the malignancies that can affect the oral cavity. Correct diagnosis and the establishment of an ideal clinical approach are essential for the patient's life expectancy and good prognosis.